Molecular Regulation of the Mitochondrial F(1)F(o)-ATPsynthase: Physiological and Pathological Significance of the Inhibitory Factor 1 (IF(1)) - Faccenda, Danilo (Hindawi Publishing Corporation, 2012)
In mammals, the mitochondrial F(1)F(o)-ATPsynthase sets out the energy homeostasis by producing the bulk of cellular ATP. As for every enzyme, the laws of thermodynamics command it; however, it is privileged to have a dedicated molecular regulator that controls its rotation. This is the so-called ATPase Inhibitory Factor 1 (IF(1)) that blocks its reversal to avoid the consumption of cellular ATP when the enzyme acts as an ATP hydrolase. Recent evidence has also demonstrated that IF(1) may control the alignment of the enzyme along the mitochondrial inner membrane, thus increasing the interest for the molecule. We conceived this review to outline the fundamental knowledge of the F(1)F(o)-ATPsynthase and link it to the molecular mechanisms by which IF(1) regulates its way of function, with the ultimate goal to highlight this as an important and possibly unique means to control this indispensable enzyme in both physiological and pathological settings.